Advances in understanding the molecular mechanisms that maintain normal haemostasis. (28th March 2019) - O'Donnell, James S.; O'Sullivan, Jamie M.; Preston, Roger J. S.
Summary: Blood clot formation to stem bleeding from an injured blood vessel arises from a complex series of cellular and biochemical events, which, when dysregulated, predispose to an increased risk of thrombosis or bleeding. Similarly, haemostatic regulation of clot growth and size is exquisitely controlled by a series of anticoagulant 'checkpoints', that exert their inhibitory activity at distinct stages in the steps leading to clot formation. Although the major plasma protein constituents required for haemostasis have now been largely elucidated and the molecular events that lead to clot formation are well understood, defining a fuller appreciation of the importance, location and regulation of each haemostatic process remains a fertile area of ongoing research. In this review article, we first provide an overview of the original 'waterfall' or 'cascade' hypothesis of blood coagulation as it was defined in the 1960s. We subsequently discuss how this original model has been refined over time to incorporate accumulating data that has enabled a more nuanced consideration of the role of specific proteins, receptors and lipids in dictating the spatial and temporal development of a blood clot.